Effects of different scouring methods on the catalytic efficiency of pectinase for cotton knitted fabrics - Xiaokang, Zhao; Haitao, Ren; Jianyong, Liu (Textile research journal, 2019)
The application of bioscouring in cotton knitted fabrics should be improved owing to being a time-consuming process. In order to accelerate the bioscouring rate and shorten the bioscouring process, a repeated padding method is used on cotton knitted fabrics. The effect of the repeated padding with pectinase was studied by using FE-SEM and FTIR, and the catalytic rate was measured at different reaction temperatures, pick-up, and soaking times. The results observed in this study showed that during the bioscouring process for cotton knitted fabrics, the average catalytic rate of the repeatedly padding method was sixfold faster than the impregnation method, and the process time (15 min) decreased by 65 minutes compared with the impregnation method (80 min); the processing time was shortened to one-sixth of the impregnation method. Furthermore, the wettability of cotton knitted fabrics was better than those treated via impregnation. In the repeated padding process, with the soaking time increasing from 5 s to 25 s, the produced reducing sugar concentration increased from 1.71 mg/ml to 3.60 mg/ml in the same process time; with the pick-up increased from 50% to 90%, the produced reducing sugar concentration first increased from 1.99 mg/ml to 3.60 mg/ml, then decreased to 1.86 mg/ml. When the pick-up was about 70%, the catalytic rate of pectinase reached the best value (0.24 mg/ml/min).